DNA Polymerase Iota Promotes Esophageal Squamous Cell Carcinoma Proliferation Through Erk-OGT-Induced G6PD Overactivation - Su, Zhenzi; Gao, Aidi; Li, Xiaoqing; Zou, Shitao; He, Chao; Wu, Jinchang; Ding, Wei-Qun; Zhou, Jundong (Frontiers in Oncology, 2021)
Esophageal squamous cell carcinoma (ESCC) is one of the most lethal cancers with rapid progression and a high mortality rate. Our previous study demonstrated that DNA polymerase iota (Pol ι) is overexpressed in ESCC tumors and correlates with poor prognosis. However, its role in ESCC proliferation remains obscure. We report here that Pol ι promotes ESCC proliferation and progression through Erk-OGT regulated G6PD overactivation. Cell proliferation was assessed by colony formation and EdU incorporation assay. Our transcriptome data was reanalyzed by GSEA and validated by analysis of cellular metabolism, G6PD activity, and cellular NADPH concentration. The level of Pol ι, OGT, G6PD and O-GlcNAcylation in ESCC cells and patient samples was analyzed. The Erk inhibitor PD98059 was applied to confirm OGT expression regulation by the Erk signaling. The G6PD inhibitor polydatin was used to examine the role of G6PD activation in Pol ι promoted proliferation. We found that Pol ι promotes ESCC proliferation. It shunted the glucose flux towards the pentose phosphate pathway by activating G6PD through OGT-promoted O-GlcNAcylation. The expression of OGT was positively correlated with Pol ι expression and O-GlcNAcylation. Notably, elevated O-GlcNAcylation was correlated with poor prognosis in ESCC patients. Pol ι was shown to stimulate Erk signaling to enhance OGT expression, and the G6PD inhibitor polydatin attenuated Pol ι induced tumor growth in vitro and in vivo. In conclusion, Pol ι activates G6PD through Erk-OGT-induced O-GlcNAcylation to promote the proliferation and progression of ESCC, supporting the notion that Pol ι is a potential biomarker and therapeutic target of ESCC.